An examination of house price movements in Queensland resource communities. (3rd May 2020) - Connell-Variy, Theodore; McGough, Tony
ABSTRACT: Successive mining "booms" have created wide-ranging, long-term socioeconomic impacts in many parts of Australia. Property markets were both directly and indirectly affected by the mining booms. Towns associated with mining activities experienced significant, rapid shifts in supply and demand levels for housing as well as changes to the amount and type of development occurring. The most recent "mining boom" in Queensland impacted on housing market dynamics, with impacts evident at all stages of the resource cycle. Housing markets were also indirectly affected by new actors and new drivers for buying property in these markets – as an investment. This paper aims to show that the "mining boom" was only one stage of a more complete cycle, and the impacts of this resource cycle on housing were particularly nuanced. Even in the short term, the importance of housing market stability-particularly measured through availability and affordability is important to the wellbeing of a town, and the underlying community. During the most recent cycle, housing markets in Queensland mining towns were uniquely affected.